TEACHER CHALLENGES IN IMPLEMENTING TBL (TASK-BASED LEARNING) - Kalayo Hasibuan; Annisa Reni Amanda Putri; Shandy Dwi Ramadhani; Annisa Herlen Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Task-Based Learning (TBL) is one of the language teaching approaches that emphasizes the use of meaningful tasks to improve students’ communication skills. This study aims to identify the challenges faced by teachers in implementing TBL in the classroom. The method used in this paper is descriptive qualitative through literature review and analysis of previous studies related to TBL implementation. The findings show that teachers experience several obstacles, including limited understanding of TBL concepts, lack of time management, students’ low participation, large classroom sizes, and insufficient teaching resources. In addition, teachers often face difficulties in designing appropriate tasks that match students’ proficiency levels. Despite these challenges, TBL remains an effective approach in enhancing students’ engagement and communication abilities when implemented properly. Therefore, teacher training, adequate facilities, and institutional support are necessary to maximize the implementation of TBL in language learning.